Synthesis, Characterization and Antibacterial Activities of Cu (II) Complex of Benzylpenicillin - Otuokere, I. E.; Robert, U. F.; Igwe, K. K. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
The sudden uprising of resistant human pathogens is a challenge in current antimicrobial therapy, therefore the need to encourage the development of novel metal-based drugs The efficacy of the various organic therapeutic agents can often be enhanced upon coordination with a suitable metal ion. Cu (II) benzylpenicillin,[Cu(Bpen)] complex was synthesized by the reaction of benzylpenicillin with CuCl2.2H2O. The complex was characterized by melting point, solubility, colour, conductivity, elemental analysis, infrared, UV/Visible, 1HNMR and 13CNMR spectroscopy. The spectral data showed that the ligand benzylpenicillin behaved as a pentadentate ligand coordinating to the metal ion through OH, C=O of amide, C-O of ?-lactam, C=O of COOH and NH. A trigonal bypyramidal geometry have been proposed for [Cu(Bpen)]. The ligand and [Cu(Bpen) complex have been screened for their in vitro antibacterial activity against four gram positive strains (Staphyloccocus aureus, Bacillus substilis, Bacillus cereus and Enterococus feacalis) and four gram negative (Escherichia coli, Enterobacter clocae, Pneumonia aeruginosa and Campylobacter felus). It was deduced that [Cu(Bpen)] complex have improved antibacterial activity than benzylpencillin alone and it was evident that the overall potency of benzylpencillin was enhanced on coordination with copper ion.